Peningkatan Kemampuan Guru Mata Pelajaran Bahasa Arab dalam Membuat Media Pembelajaran melalui Workshop pada Madrasah Binaan di Kec. Samigaluh Kulon Progo - Abdul Hamid Tarwaca (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
Professional teachers have four components as described in UU No. 19 year 2003 about teachers and lecturers. One of them is pedagogic competence that demands teachers to be able to perform the learning well. Learning can be done well if the teacher can plan/design the learning systematically and carefully. One component that needs to get noticed in learning planning is the selection of appropriate learning media. PTKp aims to test the ability of teachers in the creation of learning media to improve the competence of teachers in Arabic subjects in the sub-districts Samigaluh. The study was conducted in two cycles. The main cycle of media creations is learning Arabic and its use in learning. The results showed that the implementation of a learning media making workshop was very effective to improve teachers' ability in Arabic language learning. Furthermore, that this workshop continues to be developed in the madrasah need attention and cost assistance from the madrasah and or the ministry of religious district Kulon Progo.